KAMPUNG PECUT” WEBSITE AS A MEANS OF CULTURE PROMOTION IN THE DIGITAL ERA - Andi Basuki; Etty Soesilowati; Siti Mas’ula; Muhammad Aris Ichwanto; Dewi Ayu Sakdiyyah; I Wayan Bayu Wiarta (Yayasan Education and Social Center, 2022)
Packaging Village, Kediri City District is one of the areas in Kediri City, which is famous for its cultural arts village, especially Jaranan. So many people know it as the